Ozone assisted autohydrolysis of wheat bran enhances xylooligosaccharide production with low generation of inhibitor compounds: a comparative study - Sonkar, Rutuja Murlidhar; Gade, Pravin Savata; Bokade, Vijay; Mudliar, Sandeep N.; Bhatt, Praveena (Bioresource Technology, 2021)
In the present study, ozone assisted autohydrolysis (OAAH) was evaluated for enhanced generation of xylooligosaccharide (XOS) from wheat bran. The total XOS yield with optimum ozone dose of 3% (OAAH-3) was found to be 8.9% (w/w biomass) at 110 degrees C in comparison to 7.96% at 170 degrees C by autohydrolysis (AH) alone. Although, there was no significant difference in oligomeric composition (DP 2-6), significant decrease in degradation products namely furfural (2.78-fold), HMF (3.15-fold), acrylamide (nil) and acetic acid (1.06-fold), was observed with OAAH-3 as a pretreatment option. There was 1-fold higher xylan to XOS conversion and OAAH-hydrolysate had higher DPPH radical scavenging activity than AH. PCA plots indicated clear enhancement in XOS production and lower generation of inhibitors with decrease in treatment temperature. Results of the study therefore suggest OAAH can be an effective pretreatment option that can further be integrated with downstream processing for concentration and purification of XOS.
Keywords: Advanced oxidation; Agro-industry waste; hydrothermal treatment; Ozonolysis; Xylooligosaccharide

Effect of furfural, acetic acid and 5-hydroxymethylfurfural on yeast growth and xylitol fermentation using Pichia stipitis NCIM 3497 - Bhavana, B. K.; Mudliar, Sandeep N.; Bokade, V. V.; Debnath, S. (Biomass Conversion and Biorefinery, 2024)
The valorization of C5 sugars (xylose) from hemicellulose of agro-industrial residues to xylitol, as one of the multi-products biorefinery approach, mandates the pretreatment of biomass which releases fermentable sugars along with the generation of biological inhibitors affecting xylitol fermentation. This study was therefore evaluated to understand the inhibitory kinetics of furfural, 5-hydroxymethylfurfural and acetic acid on xylitol fermentation. Xylitol fermentation was established using Pichia stipitis NCIM 3497 with xylose as a pure substrate optimized for xylitol yield and productivity of 0.48 g/g of xylose and 0.13 g/L/h, respectively. The functional relationship of yeast specific growth rate and limiting substrate (xylose) was expressed by Monod-type kinetics. The inhibition kinetics results indicated that the effect of inhibitors on xylitol fermentation was furfural > acetic acid > HMF. Furfural (500 mg/L) and acetic acid (1000 mg/L) reduced xylitol yield by 59% and 44%, respectively, with least reduction of 9.89% exhibited by HMF. The synergistic effect of 500 mg/L furfural, 500 mg/L HMF and 1000 mg/L acetic acid showed the highest reduction in xylitol yield of 67.6% as compared to the control. Kinetic studies predicted that the maximum concentration of furfural, HMF and acetic acid which inhibited P. stipitis growth was 884 mg/L, 3258 mg/L and 2922 mg/L, respectively, whereas xylitol production was completely inhibited at 1069 mg/L furfural, 3498 mg/L HMF and 3714 mg/L acetic acid. Furfural and acetic acid were found to be a competitive inhibitor, while uncompetitive inhibition was observed with HMF indicating negligible effect on xylitol fermentation.
Keywords: Acetic acid; furfural; HMF; Inhibition kinetics; Pichia stipitis; Xylitol fermentation